Targeting Oxidative Stress Injury after Ischemic Stroke in Conscious Rats: Limited Benefits with Apocynin Highlight the Need to Incorporate Long Term Recovery - Robert M. Weston; Bin Lin; Gregory J. Dusting; Carli L. Roulston (Stroke Research and Treatment)
NADPH oxidase is a major source of superoxide anion following stroke and reperfusion. This study evaluated the effects of apocynin, a known antioxidant and inhibitor of Nox2 NADPH, on neuronal injury and cell-specific responses to stroke induced in the conscious rat. Apocynin treatment (50 mg/kg i.p.) commencing 1 hour prior to stroke and 24 and 48 hours after stroke significantly reduced infarct volume in the cortex by ~ 60%, but had no effect on striatal damage or neurological deficits. In situ detection of reactive oxygen species (ROS) using dihydroethidium fluorescence revealed that increased ROS detected in OX-42 positive cells following ischemia was reduced in apocynin-treated rats by ~ 51%, but surprisingly increased in surrounding NeuN positive cells of the same rats by ~ 27%, in comparison to the contralateral hemisphere. Reduced ROS from activated microglia/macrophages treated with apocynin was associated with reduced Nox2 immunoreactivity without change to the number of cells. These findings confirm the protective effects of apocynin and indicate a novel mechanism via reduced Nox2 expression. We also reveal compensatory changes in neuronal ROS generation as a result of Nox2 inhibition and highlight the need to assess long term individual cell responses to inhibitors of oxidative stress.